Pengembangan Sistem Absensi Karyawan Berbasis Website Dengan Metode Rapid Application Development (RAD) Di PT. Buana Citra Internusa - Reddy Alfayed; Juliandri; Hanna Willa Dhany (Jurnal Komputer Teknologi Informasi Sistem Komputer (JUKTISI), 2025)
Manual or disconnected management of employee attendance and payroll often leads to various issues, such as data inaccuracy, process delays, and lack of efficiency in attendance recording and salary calculation. PT. Buana Citra Internusa, as a growing company, requires an integrated system capable of handling employee administration quickly and accurately. This study aims to develop a web-based employee attendance system integrated with payroll using the Rapid Application Development (RAD) method. RAD was chosen because it accelerates the development process through iterative and collaborative stages between developers and end-users. The system is designed to support automatic daily attendance recording and integrate it with the payroll module based on attendance data, job positions, and working hours. Key features developed include user login, employee data management, attendance recording, working hour configuration, salary calculation, and payroll reporting. System testing was carried out using the black-box method to ensure all functions operate as expected. The development results show that the system significantly improves the efficiency of attendance and payroll management compared to previous methods. It also provides easier access, data transparency, and reduces the potential for human error. With this system, PT. Buana Citra Internusa can carry out employee administrative processes more effectively and in a more controlled manner